The Effect Of Qur'anic Murottal Therapy On Postpartum Blues During The Puerperium - Tonasih, Tonasih; Widayanti, Wiwin; Ratnawati, Julia (Greenation Publisher & Yayasan Global Research National, 2023)
In general, postpartum mothers only get the fulfillment of their physiological needs so it is very influential on the decline in the psychological condition of postpartum mothers called the postpartum blues. The study was conducted to determine the influence of Murotal Al Quran on the incidence of postpartum blues. The method used is pre-experimental research with one group pretest and posttest design experiment using questionnaires. Experimental research is research that aims to describe the effect of a treatment or treatment as an independent variable on the results of treatment as a dependent variable. Most postpartum mothers who experience Postpartum Blues are in the age group of 20-35 years, Housewives (IRT), junior high school education, parity of the first child, and in the normal childbirth group. There is an influence of Qur'anic Murottal Therapy on the incidence of postpartum blues in postpartum mothers in the UPTD Working Area of the Tukdana Health Center, Indramayu Regency in 2022.